"Keep the faith": Spirituality as a contributor to resiliency in five elderly people. Issue 4 (2nd October 2018) - Sytsma, Terin T.; Schmelkin, Leah A.; Jenkins, Sarah M.; Lovejoy, Laura A.; Lapid, Maria I.; Piderman, Katherine M.
ABSTRACT: Spirituality is an important component of spiritual well-being (SWB) and quality of life in the elderly. The Hear My Voice study explores the impact of spiritual life review and spiritual legacy document (SLD) formation on people with advanced diseases, including the elderly. Interview transcripts and SLDs of five participants ≥80 years were reviewed. Cases were summarized with an emphasis on spirituality and resiliency. Follow-up survey results were analyzed. Common themes included spirituality providing comfort, strength, community, and inspiration. Trends toward improved SWB and faith were detected after life review and SLD formation. Satisfaction surveys indicated greater sense of meaning post-intervention.